Anti-tumor necrosis factor-induced lupus in patients with inflammatory bowel disease: a hospital-based cohort study from Korea. (March 2021) - Choi, Su Jin; Ahn, Soo Min; Oh, Ji Seon; Hong, Seokchan; Lee, Chang-Keun; Yoo, Bin; Ye, Byong Duk; Yang, Suk-Kyun; Park, Sang Hyoung; Kim, Yong-Gil
Background: Anti-tumor necrosis factor (TNF) agents are increasingly used for rheumatic diseases and inflammatory bowel disease (IBD), but are associated with the development of anti-TNF-induced lupus (ATIL). Nonetheless, few ATIL studies on non-Caucasian IBD patients exist. Here, we investigated the incidence, clinical features, and risk factors of ATIL in Korea. Methods: We retrospectively reviewed the medical records of IBD patients undergoing anti-TNF therapy at our tertiary IBD center between 2008 and 2020. ATIL was diagnosed as a temporal association between symptoms and anti-TNF agents, and the presence of at least one serologic and non-serologic American College of Rheumatology criterion. The risk factors for ATIL occurrence were assessed using multivariate Cox regression analysis. Results: Of 1362 IBD patients treated with anti-TNF agents, 50 (3.7%) ATIL cases were suspected, of which 14 (1.0%) received a definitive diagnosis. Arthritis and mucocutaneous symptoms were observed in 13 and 4 patients, respectively. All ATIL cases were positive for anti-nuclear and anti-dsDNA antibodies. Four patients (30.8%) improved while continuing anti-TNF therapy. At the final follow up, the ATIL group ( n = 14) had a lower IBD remission rate (30.8% versus 68.8%, p = 0.019) than the non-ATIL group ( n = 36). Ulcerative colitis and longer disease duration were associated with ATIL occurrence, with hazard ratios of 7.017 ( p = 0.005) and 1.118 ( p = 0.002), respectively. Conclusion: Although rare, ATIL is associated with poor treatment response to IBD in Korean patients. ATIL should be considered if arthritis and mucocutaneous symptoms develop during anti-TNF therapy for IBD.